Single-Dose Universal Hepatitis A Immunization in Argentina: Low Viral Circulation and High Persistence of Protective Antibodies Up to 4 Years - Vizzotti, Carla (2015)
Fil: Vizzotti, Carla. Ministerio de Salud de la Nación, Ciudad Autónoma de Buenos Aires; Argentina.